2016
DOI: 10.1111/1440-1681.12660
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of aspirin against interferon‐α‐2b—induced depressive behavior in Sprague Dawley rats

Abstract: Accumulating data advocates that inflammatory mediators may contribute to depression in experimental models as well as in humans. Nonetheless, whether anti-inflammatory treatments can prevent depression still remains controversial. To substantiate our hypothesis, we used an interferon-α-2b model of depression using Sprague Dawley rats. Interferon-α-2b is a cytokine which activates immune response and also produces depression. The animals were treated for 21 days with aspirin (10 mg/kg, per oral (p.o.)) dexamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…6 Aspirin was associated with increased sucrose preference and reduced immobility in the forced swim test, as well as decreased cortisol levels and increased brain serotonin levels in an interferon model of depression in Sprague Dawley rats, suggesting both clinical model efficacy and influences on salient pathways. 38 Several pharmacoepidemiology studies suggest that people taking aspirin may have a lower risk for depression, 33,34,39,40 notwithstanding some conflicting data that have failed to show a benefit of aspirin. 41,42 Early clinical trials of aspirin in mood disorders have also generated promising but preliminary signals of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Aspirin was associated with increased sucrose preference and reduced immobility in the forced swim test, as well as decreased cortisol levels and increased brain serotonin levels in an interferon model of depression in Sprague Dawley rats, suggesting both clinical model efficacy and influences on salient pathways. 38 Several pharmacoepidemiology studies suggest that people taking aspirin may have a lower risk for depression, 33,34,39,40 notwithstanding some conflicting data that have failed to show a benefit of aspirin. 41,42 Early clinical trials of aspirin in mood disorders have also generated promising but preliminary signals of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoattractant receptor-homologous molecule expressed on T helper type 2 cells (CRTH2) is a PG D 2 receptor that is also involved in the behavioral effects of LPS ( 206 , 207 ). Inhibition of PG synthesis by nonsteroidal antiinflammatory drugs attenuates the sickness and depression-like behavior induced by LPS, Bacille Calmette–Guérin and interferon-α-2b ( 204 , 208 211 ). Cyclooxygenase-2 inhibitors, particularly celecoxib, have the potential to ameliorate depression in humans, although a meta-analysis of the pertinent clinical trials points out that the subgroup of patients who could benefit from such therapy has not yet been identified ( 212 ).…”
Section: Impact Of Immune Stress Signaling From the Periphery On Braimentioning
confidence: 99%
“…Depression and inflammation, two major diseases that affect millions of people worldwide, have been shown these late years to be connected to each other due to biological, hormonal, or environmental factors. While on the one hand some studies demonstrated that pro-inflammatory cytokines, markers increased in the case of inflammation, can induce behavioral sicknesses, , on the other hand some depressed patients were found to present high serum levels of pro-inflammatory cytokines . This interconnection has also been suggested during clinical investigations where the antidepressant (AD) activity of some anti-inflammatory (AI) drugs such as acetyl salicylic acid (aspirin) or celecoxib has been revealed. Similarly, some AI properties have also been attributed to desipramine and fluoxetine, two widely used AD molecules …”
mentioning
confidence: 94%